Money and the Decentralization of Exchange - Ostroy, Joseph M.; Starr, Ross M. (Econometrica, 1974)
A pairwise trading process is formulated subject to conditions of nonnegativity of traders' holdings and quid pro quo. It is shown that that: (i) There is a centralized procedure that achieves the equilibrium allocation for an arbitrary economy. (ii) It is not in general possible to find a decentralized procedure that achieves the equilibrium allocation for an arbitrary economy. (iii) In a monetary economy there is a decentralized procedure that achieves the equilibrium allocation. The usefulness of money is that it allows decentralization of the trading process.